The violation of human rights in the prison system: An analysis based on gender and vulnerable groups (Revista Direitos Humanos e Democracia, 2026)
This article sought to discuss and analyze human rights violations in the Brazilian prison system, characterized by the systematic infringement of the fundamental rights of the incarcerated population. The analysis emphasizes the structural inequalities faced by prisoners, especially women, people with disabilities, the elderly, and the LGBTQIA+ population. The research, of a qualitative-quantitative nature, uses secondary data from SISDEPEN and the National Human Rights Ombudsman, supplemented by a literature review. It was observed that, although the majority of the prison population is male, women show a higher proportion of violations. A shortage of adequate structures in prison units to meet the needs of groups considered most vulnerable was also identified. The analysis reveals the perpetuation of an exclusionary prison model that intensifies social inequalities and undermines human dignity. It is concluded that the current system reinforces inequalities and necessitates more inclusive public policies aimed at resocialization.
Keywords: : Human Rights; Prison System; Social Vulnerability